2016
DOI: 10.5296/ifb.v3i2.9936
|View full text |Cite
|
Sign up to set email alerts
|

Bank-Specific and Macroeconomic Determinants of Commercial Banks Profitability in Ghana

Abstract: This study examines the influence of bank-specific and macroeconomic factors on commercial banks profitability in Ghana. The study employed the ordinary least square regression model to analyse the data obtained from the annual financial statements of five commercial banks from 2010 to 2015. The empirical results suggest that bank size, liquidity, capital adequacy, asset management, expense management, and real interest rate are positively related to profitability. GDP growth and inflation rate on the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…Various studies revealed that size positively affects the profitability of the banks inspected, such as Abobakr (2018), Kawshala and Panditharathna (2017), Menicucci et al, (2016), Yakubu (2016), Pradhan and Shrestha (2016), and Ally (2014). Mostly, prior studies on the effect of bank size on its profitability line with the argument that larger banks benefit from economies of scale and cost reduction (Ben Naceur and Goaied, 2008;Bourke, 1989;Molyneux and Thorton, 1992;Bikker and Hu, 2002;Goddard et al, 2004aGoddard et al, , 2004b, therefore they are expected to have higher levels of performance than smaller banks.…”
Section: Bank Sizementioning
confidence: 99%
“…Various studies revealed that size positively affects the profitability of the banks inspected, such as Abobakr (2018), Kawshala and Panditharathna (2017), Menicucci et al, (2016), Yakubu (2016), Pradhan and Shrestha (2016), and Ally (2014). Mostly, prior studies on the effect of bank size on its profitability line with the argument that larger banks benefit from economies of scale and cost reduction (Ben Naceur and Goaied, 2008;Bourke, 1989;Molyneux and Thorton, 1992;Bikker and Hu, 2002;Goddard et al, 2004aGoddard et al, , 2004b, therefore they are expected to have higher levels of performance than smaller banks.…”
Section: Bank Sizementioning
confidence: 99%
“…The coefficient of bank size is positively and statistically significant, suggesting that large banks harvest the benefits of economies of scale and, thus, they are more profitable than their small counterparts. Abdullah et al (2014) have also documented the positive link between banks' size and performance. These results suggest that banks can increase their financial performance by increasing their size and reducing CR.…”
Section: Results Of Banks' Performance Modelmentioning
confidence: 91%
“…They also showed that only the real interest rate affects banks' performance positively and significantly. Abdullah, Parvez, and Ayreen (2014) analyzed the profitability of 26 banks listed on Dhaka Stock Exchange in Bangladesh over the period from 2008-2011. They found sig-nificant and positive impacts of bank size, cost efficiency, capitalization, and higher concentration on ROA and NIM.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This reform helped the country to increase the number of banks operating. The Africa Banking Survey in 2014, annual report stated that a maximum of 28 banks including domestic and foreign were in operation, non-banking institutions were reported to be 58, and 137 consists of rural and community banks [32] .…”
Section: Banking Sectormentioning
confidence: 99%